PENGARUH MODEL BAMBOO DANCING BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR RANAH KOGNITIF IPA SISWA KELAS V SD - Baskoro, Baskoro; Murdani, Eka; Sumarli, Sumarli (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the effect of the Bamboo Dancing learning model assisted by Wordwall media on the cognitive learning outcomes of fifth-grade students. This research employed a quantitative experimental method with a quasi-experimental design. The population consisted of all fifth-grade students, totaling 42 students, and the sample was determined using a saturated sampling technique. Data were collected using test and non-test techniques. The test instrument was an essay-type cognitive learning outcome test consisting of five questions on the “food chain” topic, while the non-test instrument was a student activity observation sheet. Data were analyzed using the independent sample t-test, effect size calculation, and percentage of student activity. The results showed that: (1) there was a significant difference in students’ cognitive learning outcomes between the class using the Bamboo Dancing model assisted by Wordwall and the class using direct instruction, with a significance value (2-tailed) of 0.002 < 0.05; (2) the Bamboo Dancing model assisted by Wordwall had a strong effect on students’ cognitive learning outcomes, with an effect size of 1.035 (high category); and (3) student activity during learning reached 82.14%, categorized as very active. Therefore, it can be concluded that the Bamboo Dancing model assisted by Wordwall positively influences students’ cognitive science learning outcomes in fifth grade.